AN ANALYSIS OF ENGLISH THESIS WRITING: A Case Study of English Department of UIN Sunan Gunung Djati Bandung - Andang Saehu (University of Kuningan, 2013)
Abstract: This is a report of a study designed to examine the process of thesis—a final (research-based) paper for undergrads prior to academic completion—writing of English Department students who graduated in Academic Year 2007/2008. Using a descriptive method, this case study aimed to describe the stages, to identify the problems, and to explore the techniques of solving problems used by respondents in the thesis writing by involving six students who had engaged in writing and research project course. The data concerning writing stages, problems, and coping with strategies were collected by using questionnaires, interviews, and documentation (thesis). The results showed that all participants went through the thesis writing stages determined by Faculty of Adab of UIN Sunan Gunung Djati, Bandung, namely: 1) Starting process; 2) Researching; 3) Reporting; and 4) Doing consultation. These also showed that all respondents encountered: 1) Procedural problems, which were likely to be the major problems shared by all respondents; 2) Academic problems; and 3) Non-academic problems. However, whatever problems they dealt with, each of them had his/her own strategies to cope with. The procedural and academic problems were coped with by reading, doing consultation, and peer-collaboration. Meanwhile, non-academic problems were solved by having a rest and managing time.Keywords: analysis, thesis, stages, problems, and solutions